O integracji opozycyjnych paradygmatów nauk społecznych. Próba rewizji założeń nie-Marksowskiego materializmu historycznego - Ciesielski, Mieszko (Człowiek i Społeczeństwo, 2016)
The author embarks on the issue of integration of paradigms developed within social sciences. Usually, theoreticians distinguish three pairs of opposing paradigms: materialism/idealism, holism/individualism, and antagonism/solidarism. The papers argues that Leszek Nowak’s theory of non-Marxian historical materialism, after a revision of some of its underlying conceptual premises, might become a theory which overcomes one-sidedness of particular paradigms. The author’s view is that modification of two premises, i.e. radical materialism, antagonistic notion of social being will make it possible to formulate a general social theory which integrates the paradigms in question. The article outlines the idea of a general social theory construed in this fashion.